2011
DOI: 10.1089/ars.2010.3241
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman Primate Models of Human Immunology

Abstract: Nonhuman primates have been used for biomedical research for several decades. The high level of genetic homology to humans coupled with their outbred nature has made nonhuman primates invaluable preclinical models. In this review, we summarize recent advances in our understanding of the nonhuman primate immune system, with special emphasis on studies carried out in rhesus macaque (Macaca mulatta). We highlight the utility of nonhuman primates in the characterization of immune senescence and the evaluation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 108 publications
2
107
0
Order By: Relevance
“…In this case, the desired clinical benefit is enhanced survival or prevention of major morbidity after exposure to potentially lethal doses of radiation across the hematopoietic acute radiation subsyndrome (USFDA 2014a). The non-human primate (NHP), rhesus macaque, is a relevant animal for the development of models that mimic the human response to the acute radiation syndrome (ARS) and the delayed effects of acute radiation exposure (DEARE) as well as treatment of the hematopoietic (H)-ARS, the gastrointestinal (GI)-ARS, immune reconstitution, prolonged GI damage, and delayed lung injury characteristic of the delayed effects DEARE (Monroy et al 1986;Gibbs et al 2007;Nikolich-Zugich 2007;MacVittie et al 2012aMacVittie et al and b, 2014MacVittie et al , 2015Farese et al 2012a;Herodin et al 2005;Messaoudi et al 2011;Garofalo et al 2014a and b;Hankey et al 2015;Thrall et al 2013Thrall et al , 2015. In this regard, the NHP, a well-characterized model, is a likely choice for defining the efficacy of MCM and conducting pivotal efficacy studies under the criteria of the FDA AR.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the desired clinical benefit is enhanced survival or prevention of major morbidity after exposure to potentially lethal doses of radiation across the hematopoietic acute radiation subsyndrome (USFDA 2014a). The non-human primate (NHP), rhesus macaque, is a relevant animal for the development of models that mimic the human response to the acute radiation syndrome (ARS) and the delayed effects of acute radiation exposure (DEARE) as well as treatment of the hematopoietic (H)-ARS, the gastrointestinal (GI)-ARS, immune reconstitution, prolonged GI damage, and delayed lung injury characteristic of the delayed effects DEARE (Monroy et al 1986;Gibbs et al 2007;Nikolich-Zugich 2007;MacVittie et al 2012aMacVittie et al and b, 2014MacVittie et al , 2015Farese et al 2012a;Herodin et al 2005;Messaoudi et al 2011;Garofalo et al 2014a and b;Hankey et al 2015;Thrall et al 2013Thrall et al , 2015. In this regard, the NHP, a well-characterized model, is a likely choice for defining the efficacy of MCM and conducting pivotal efficacy studies under the criteria of the FDA AR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed in rhesus macaques have shown that transitional and effector memory subsets are present within the CD28+ CD95+ population and can be identified by including an additional phenotypic marker, such as CCR7 [24,25]. Thus, the delineation of specific memory T cell populations according to CD95 and CD28 expression alone may not accurately define true central and effector memory T cells subsets.…”
Section: Resultsmentioning
confidence: 99%
“…Rhesus macaques and baboons both share a high degree of sequence similarity with humans, but do not have MHC-C loci (Messaoudi et al, 2011;Moffett and Loke, 2006;Prillman et al, 1996). Depending on the specific allele, rhesus macaques share an 80%-99% sequence identity with humans at the HLA loci (Doerks et al, 2002).…”
Section: Comparative Sequence Identity and Functionality Of The Majormentioning
confidence: 99%